Disruption of Phthorimaea operculella (Lepidoptera: Gelechiidae) oviposition by the application of host plant volatiles. Issue 4 (9th August 2013) - Anfora, Gianfranco; Vitagliano, Silvia; Larsson, Mattias C; Witzgall, Peter; Tasin, Marco; Germinara, Giacinto S; De Cristofaro, Antonio
Abstract BACKGROUND Phthorimaea operculella is a key pest of potato. The authors characterised the P. operculella olfactory system, selected the most bioactive host plant volatiles and evaluated their potential application in pest management. The electrophysiological responses of olfactory receptor neurons (ORNs) housed in long sensilla trichodea of P. operculella to plant volatiles and the two main sex pheromone components were evaluated by the single‐cell recording (SCR) technique. The four most SCR‐active volatiles were tested in a laboratory oviposition bioassay and under storage warehouse conditions. RESULTS The sensitivity of sensilla trichodea to short‐chained aldehydes and alcohols and the existence of ORNs tuned to pheromones in females were characterised. Male recordings revealed at least two types of ORN, each of which typically responded to one of the two pheromone components. Hexanal, octanal, nonanal and 1‐octen‐3‐ol significantly disrupted the egg‐laying behaviour in a dose‐dependent manner. Octanal reduced the P. operculella infestation rate when used under storage conditions. CONCLUSIONS This work provides new information on the perception of plant volatiles and sex pheromones by P. operculella. Laboratory and warehouse experiments show that the use of hexanal, octanal, nonanal and 1‐octen‐3‐ol as host recognition disruptants and/or oviposition deterrents for P. operculella control appears to be a promising strategy. © 2013 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.